Indicadores epidemiológicos e imunofarmacológicos da associação entre complicações da covid-19 e câncer de mama - Hertz, Everaldo (2024)
Introduction:Epidemiological evidence related to the COVID-19 pandemic suggests that the morbidity-mortality risk in cancer patients due to SARS-CoV-2 infection might be influenced by the type of cancer. Specifically, breast cancer (BC) may be associated with a lower risk of complications and death from COVID-19. However, it remains necessary to determine whether this lower susceptibility to infection is a phenomenon limited to specific regions of the world or if it could be universal. One possible hypothesis to explain a lower risk to SARSCoV-2 in women with BC is the immunomodulatory influence of certain chemotherapeutic agents, which might inhibit or attenuate the cytokine storm triggered by COVID-19. This could be the case with paclitaxel (PTX), a first-line treatment for BC.Thus, the present study had two objectives: the first was to evaluate the association between the diagnosis of BC and other cancer types with the mortality risk in patients hospitalized due to COVID-19 infection. The second was to assess, under in vitro conditions, whether the inflammatory response to exposure to attenuated SARS-CoV-2 could be modulated by PTX. The results of the first study were published in the journal Contribuciones a las Ciencias Sociales (Qualis A4). This study involved conducting a retrospective epidemiological analysis using data from patients hospitalized for Severe Acute RespiratorySyndrome (SARS) resulting from SARS-CoV-2 infection, obtained from the national database of acute lower respiratory disease notification forms (ARDL) between January 1 and December 2021. This period was chosen because the conditions for COVID-19 patient care had stabilized compared to 2020, and immunization rates were still relatively low compared to 2022.Pregnant and postpartum women were excluded from the analysis, and the remaining 1,048,575 patients were categorized into three groups: without a prior cancer diagnosis (WC, n=64,370), with a prior diagnosis of BC (n=1,645), and with a diagnosis of other cancer types (OC, n=2,984). In the analyses conducted, the OC group was further subdivided into eight cancer types. Mortality and other clinical complications during the hospitalization period were statistically compared between groups using analysis of variance followed by Bonferroni post hoc test and chi-square test. The influence of covariates was determined by multivariate logistic regression analysis.The results indicated that the average lethality rate (deaths/month) was highest in the OC group (58.30 ± 2.57%), intermediate in the BC group (45.47 ± 3.06%), and lowest in the WC group (40.1 ± 5.91%) (p < 0.001). The relative risk (RR) of death in the BC group was 1.461 (95% CI 1.227-1.740) compared to the WC group. Among other cancer types, only patients with non-melanoma skin cancer did not show a higher mortality risk compared to the WC group. Conversely, all other cancer types presented an RR ranging from 1.906 to 3.048 compared to the WC group. Therefore, the results supported the previous suggestion that BC could have a lower risk of morbidity and mortality from COVID-19 than other cancer types.The results of the second study were organized into a manuscript submitted to the Immunopharmacology, (Qualis A2). This study involved an in vitro protocol using the commercial human monocyte cell line THP-1. Initially, THP-1 cultures were exposed to inactivated SARS-CoV-2 virus present in the CoronaVac vaccine (CVac), and the immune response was compared with control cultures and cultures exposed to PTA (phorbol 12-O-tetradecanoylphorbol-13- acetate), a non-viral immunogenic agent. Based on pilot tests, a 24-hour culture exposure to 5% CVac was chosen, as these conditions resulted in an inflammatory activation of THP-1 cells. Five different concentrations of the chemotherapeutic PTX (10 to 300 µM) with and without activation induced by the concomitant presence of CVac and PTA were then tested.The first assay evaluated whether PTA could have a cytotoxic effect through viability analysis determined by the neutral red uptake method, based on the ability of living cells to incorporate and retain neutral red dye in their lysosomes. The results showed that PTA did not present a cytotoxic effect and, on the contrary, increased cell viability at the highest concentration (300 µM). The potential induction of cell proliferation was assessed by the MTT assay, which measures the activity of dehydrogenase enzymes, mainly succinate dehydrogenase, present in the mitochondria of viable cells. Inflammatory activation leads to an increase in cell proliferation rate, which can be observed via increased metabolic activity. In this study, exposure to CVac increased MTT activity compared to control cultures, although this effect was less than that triggered by PTA exposure. PTX exposure also significantly induced metabolic activity compared to control cultures. However, this increase was significantly lower than observed in cultures exposed to PTA and CVac.The interaction between PTX with CVac and PTX with PTA tended to decrease metabolic activity compared to cells exposed only to CVac or PTX alone, indicating an immunomodulatory activity of the chemotherapeutic agent tested. Additional analysis of PTX at 300 µM showed a significant decrease in monocyte differentiation into macrophages, observed through the formation of cell aggregates. Decreased levels of SA were also observed in cultures concomitantly treated with PTX+CVac and PTX+PTA. The expression of the pro-inflammatory cytokine TNF-α was significantly higher only in cultures exposed to PTX, while no change was observed in IL-6 expression in all treatments. These results suggested that PTX could have some level of attenuating effect on the inflammatory response triggered by SARS-CoV-2.Despite the methodological limitations related to ecological epidemiological studies, the results suggest that the lower mortality risk in women with BC hospitalized due to COVID-19 could be a universal phenomenon. Based on the evidence obtained in the second study, which also has methodological limitations related to in vitro protocols, it is possible to infer that PTX treatment could contribute in some way to reducing COVID-19 mortality risk in women with BC. However, since PTX is also used in the treatment of other cancer types, its antiinflammatory contribution might depend on the interaction with other factors present in women with and without a BC diagnosis.